2007
DOI: 10.1088/0022-3727/40/18/023
|View full text |Cite
|
Sign up to set email alerts
|

Excitation wavelength dependent fluorescence behaviour of nano colloids of ZnO

Abstract: In this paper, the fluorescence behaviour of nano colloids of ZnO has been studied as a function of the excitation wavelength. We have found that excitation at the tail of the absorption band gives rise to an emission that shifts with the change of the excitation wavelength. The excitation wavelength dependent shift of the fluorescence maximum is measured to be between 60 and 100 nm. This kind of excitation wavelength dependent fluorescence behaviour, which may appear to be in violation of Kasha's rule of exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 28 publications
(35 reference statements)
2
27
0
2
Order By: Relevance
“…The autofluorescence signals of the SC and of the applied ZnO NPs are located in the same optical range, making selective detection rather difficult even if temporal resolution of fluorescence decay is applied by time-correlated single photon counting [27,48]. To solve this problem it should be taken into consideration that various particles (crystals) including ZnO NPs possess a distinct structure, allowing an SHG/HRS signal to be generated at half the wavelength of the excitation radiation [36,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The autofluorescence signals of the SC and of the applied ZnO NPs are located in the same optical range, making selective detection rather difficult even if temporal resolution of fluorescence decay is applied by time-correlated single photon counting [27,48]. To solve this problem it should be taken into consideration that various particles (crystals) including ZnO NPs possess a distinct structure, allowing an SHG/HRS signal to be generated at half the wavelength of the excitation radiation [36,49].…”
Section: Discussionmentioning
confidence: 99%
“…According to our measurements, these authors erroneously assigned a corresponding radiation observed in the range of half the excitation wavelength to two-photon-induced fluorescence of the ZnO NPs, which was probably due to the fact that their experiments lacked spectrally resolved measurements. Fluorescence spectral profiles of ZnO NPs have a relatively bright prominent maximum red shift with respect to the electronic transition [48]. In a recent paper, Song et al [50] reported a detection limit of about 200–250 NPs of ZnO obtained under their experimental conditions optimized for fluorescence detection, which corresponded to a concentration of 5–7 fg/µm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Other materials such as silicon or chalcogenide ( n , but silicon suffers from high intrinsic normal dispersion and free carrier (FC) creation losses [29,30] and chalcogenide glass also has high normal dispersion and relatively low damage threshold (9 2 / cm GW [31,32]) compared to 5 2 O Ta [3] used as a high k -dielectric for silicon heterojunction bipolar transistors (Si-HBTs). 5 2 O Ta is a well known material to the microelectronics industry [33] with well known processing technologies, and forms a strong candidate for potential applications in nonlinear integrated optics [34][35][36][37][38], such as supercontinuum generation (SCG) [3,39,40], third harmonic generation (THG) spectroscopy [41][42][43], compact optical parametric amplifiers (OPAs) and tunable light sources as well as fluorescence detection [44][45][46].…”
mentioning
confidence: 99%
“…Egyesek a kész szolhoz adagolják a stabilitás növelésére szánt komponenst [23,24,25], mások a felületmódosító anyag jelenlétében végzik a részecskék szintézisét [26,27,28,29]. A felületmódosításhoz legelterjedtebben a különböző szilanizáló ágenseket [23,24] és polielektrolitokat, mint a PEI (polietilénimin) [28] és a PVP (polivinilpirrolidon) [24,26,27,29] alkalmazzák, de található példa egyéb anyagokra is: 1-dekántiol [27], dietanolamin [ 30 ] vagy trietanolamin [ 31 ].…”
Section: Irodalmi áTtekintésunclassified
“…A felületmódosításhoz legelterjedtebben a különböző szilanizáló ágenseket [23,24] és polielektrolitokat, mint a PEI (polietilénimin) [28] és a PVP (polivinilpirrolidon) [24,26,27,29] alkalmazzák, de található példa egyéb anyagokra is: 1-dekántiol [27], dietanolamin [ 30 ] vagy trietanolamin [ 31 ]. Wu és munkatársai [24] öt különböző anyag hatását vizsgálták.…”
Section: Irodalmi áTtekintésunclassified